2019
DOI: 10.1101/636829
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TRESK background K+ channel deletion selectively uncovers enhanced mechanical and cold sensitivity

Abstract: Changes in TRESK K + channel expression/function enhance sensory neurons excitability, but its role in somatosensory perception and nociception is poorly understood. We show that TRESK regulates the sensitivity to mechanical and cold stimuli but not the perception of heat. TRESK knockout mice nociceptive neurons present an enhanced excitability; skin nociceptive C-fibers show an increased activation by lower intensity cold or mechanical stimulation and mice lacking TRESK present mechanical and cold hypersensit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 63 publications
(192 reference statements)
3
15
0
Order By: Relevance
“…The sensitivity of DRG neurons from wild-type and TRESK KO animals to a potent TRPV1 agonist, capsaicin, was determined by using cytoplasmic calcium imaging. There was no difference in the capsaicin sensitivity of wild-type and TRESK KO neurons, which is in good agreement with a recent study comparing the responses of wild-type and TRESK KO DRG neurons to various TRP channel agonists (32).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The sensitivity of DRG neurons from wild-type and TRESK KO animals to a potent TRPV1 agonist, capsaicin, was determined by using cytoplasmic calcium imaging. There was no difference in the capsaicin sensitivity of wild-type and TRESK KO neurons, which is in good agreement with a recent study comparing the responses of wild-type and TRESK KO DRG neurons to various TRP channel agonists (32).…”
Section: Discussionsupporting
confidence: 92%
“…The K 2P channel TRESK is a major component of the background potassium current in the primary sensory neurons of the dorsal root and trigeminal ganglia. Accordingly, an increased sensitivity to various painful stimuli have been described in TRESK KO animals in different regions of the body (28)(29)(30)(31)(32) and reduced abundance of TRESK was associated with pathological pain conditions (33,34). A recent report suggested that trigeminal neurons are particularly sensitive to altered TRESK activity (29).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether KOR activation mediates temperature-dependent hypersensitivity, we recorded jumping behavior across a range of temperatures (3 o C, 10 o C, 15 o C, 20 o C, 30 o C, 42 o C) ( Fig 1A). Jumping behavior in this assay has been well-established as a measure of nocifensive behavior (Allchorne et al, 2005;Castellanos et al, 2020;Deuis et al, 2017). We show that the KOR agonist, U50 (5 mg/kg i.p.)…”
Section: Kor Activation Induces Cold Hypersensitivitymentioning
confidence: 79%
“…In this issue of The Journal of Physiology, Castellanos et al (2020) report the use of a global TRESK knockout (KO) mouse to explore the role of this channel in somatosensation. Their recordings form nociceptors isolated from TRESK KO mice confirmed previous observations that, despite displaying weaker K + current density, these neurons have a resting membrane potential that is very close to their wild-type (WT) littermates.…”
mentioning
confidence: 99%
“…When the injected depolarizing currents exceeded the AP threshold, nociceptors of TRESK KO mice fired significantly more APs, indicating that the removal of TRESK increases the excitability of nociceptors. Castellanos et al (2020) then used a Ca imaging approach to examine the sensitivity of nociceptors to common agonists. Although the responses to capsaicin and menthol did not change, responsiveness to the TRPA1 agonist allyl isothiocyanate (AITC) was significantly reduced.…”
mentioning
confidence: 99%